SAMPAH ORGANIK JADI PUPUK BERKUALITAS DENGAN AKTIVATOR BUAH SEMANGKA - Mustafa Mustafa (Jurnal Kesehatan, 2024)
Until now, not many people have utilised watermelon waste as an activator in composting. Watermelon fruit waste can have value by utilising it as liquid pukuk and as an activator. The purpose of this study was to compare the quality of compost in terms of physical parameters, such as pH, temperature, and moisture, as well as the physical quality of compost such as colour, smell and texture with watermelon fruit activator and without activator. The research method used was quasi- experiment with time series design to determine the composting process time with the addition of watermelon water. The results of this study are compost with the addition of watermelon fruit activator has the best moisture content of 40%, temperature 27°C, pH 7. In addition, based on physical observations ranging from colour, smell and texture are in accordance with SNI 19-7030-2004 while compost without activator has not met the requirements of good compost. The conclusion of this research is that compost with the addition of watermelon water activator has physical parameters that are in accordance with SNI 19-7030-2004, as well as the physical compost of colour, smell and texture. Suggestions for the community to be able to use watermelon water activator in making compost, because it is easier, simpler and environmentally friendly. For the next research, you can add cow dung to see a better compost quality.